Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai pada Kantor Balai Penyuluhan Pertanian (BPP) Kecamatan Marioriawa Kabupaten Soppeng - Hadriyanti Hadriyanti; Burhanuddin Burhanuddin; Agung Widhi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
Implementation of Human Resources Management in Improving Staff Performance at the Agricultural Extension Center (BPP) Office, Marioriawa District, Soppeng Regency (supervised by Burhanuddin and Agung Widhi Kurniawan).Soppeng Regency is located in South Sulawesi Province and is divided into 8 sub-districts, namely Marioriwawo, Lalabata, Liliriaja, Ganra, Citta, Lilirilau, Donri-Donri and Marioriawa sub-districts. As part of the agricultural sector, the Agricultural Extension Center (BPP) has an important role in providing counseling, training and guidance to farmers in increasing their productivity and welfare. The method used in this research is a quantitative method and primary data sources. Meanwhile, to analyze the data obtained, instrument tests, classical assumption tests and hypothesis tests were used with the help of SPSS 24.Based on the results of the analysis, it can be concluded that the human resource management variable has a partial effect on employee performance. The statistical calculation results of the T test show that Tcount is 19.938, meanwhile the Ttable value = 2.04, so Tcount > Ttable and the significance value is 0.000 < 0.05. The results of this analysis accept the existing hypothesis. This finding also strengthens the respondents' answers which show that every statement related to human resource management was responded to with good answers. BPP sub-district office. Marioriawa district. Soppeng, in carrying out its main duties and functions, always strives to improve its capabilities in order to achieve its planned goals. Human resource management is the process of dealing with various kinds of problems within the scope of employees' work so that they can carry out their activities to achieve the goals that have been created.